2021
DOI: 10.1159/000520560
|View full text |Cite
|
Sign up to set email alerts
|

Review of Available Data for the Efficacy and Effectiveness of Nabiximols Oromucosal Spray (Sativex®) in Multiple Sclerosis Patients with Moderate to Severe Spasticity

Abstract: Background: Sativex (USAN: nabiximols) oromucosal spray is indicated for treatment of multiple sclerosis (MS) patients with moderate to severe spasticity and inadequate response to other antispasticity medications who demonstrate clinically significant improvement during an initial trial of therapy. This narrative review investigated the efficacy and effectiveness of nabiximols oromucosal spray for moderate to severe MS spasticity by examining spasticity 010 Numerical Rating Scale (NRS) data from intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The activation of CB1 by ∆ 9 -THC is believed to mediate its anti-nausea and anti-emetic effects [169]. Sativex, which contains a combination of ∆ 9 -THC and CBD, has been used for relief of neuropathic pain in multiple sclerosis [170].…”
Section: Pharmacological Effects Of Selected Phytocannabinoidsmentioning
confidence: 99%
“…The activation of CB1 by ∆ 9 -THC is believed to mediate its anti-nausea and anti-emetic effects [169]. Sativex, which contains a combination of ∆ 9 -THC and CBD, has been used for relief of neuropathic pain in multiple sclerosis [170].…”
Section: Pharmacological Effects Of Selected Phytocannabinoidsmentioning
confidence: 99%
“…The combined use of THC and powerful CBD has shown the potential to enhance these effects, also reducing the harmful effects of THC at the level of the central nervous system. In fact, there is an FDA-approved drug called Sativex©, which is made up of an equimolar combination of these molecules and is indicated for the treatment of pain and other disorders, including multiple sclerosis [ 30 ]. We previously reported the effect of THC and CBD alone or in combination in an in vitro model carried out on three different cancer cell lines, which showed that CBD potentiated the effects of THC in terms of the inhibition of EMT proliferation and development in these three cell lines [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAFs derive from different cell types, including connective tissue-resident fibroblasts, mesenchymal cells, and even cancerous epithelial cells, which undergo extreme epithelial-to-mesenchymal transition (EMT) [ 32 ]. CAFs control the composition of the tumor stroma and induce, among other things, EMT and metastasis in lung cancer, which makes them an attractive pharmacological target in the treatment of this pathology [ 30 , 32 ]. In the present study, we show that treatment with THC and/or CBD decreases cell density and the expression of type I collagen and FSP1 in CAFs isolated from the tumors of patients diagnosed with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nabiximols (Sativex™) is a combination drug delivering a dose of 2.7 mg THC and 2.5 mg CBD with each spray and is approved to treat dry mucosa in patients with multiple sclerosis [102,111]. Some have suggested using the drug to manage chronic pain, but the medication did not meet this goal [112].…”
Section: Fda-approved Cannabinoid Formulationmentioning
confidence: 99%